Evaluation of analytical performance of the STANDARDTM M10 MPX/OPX assay for the simultaneous DNA detection and clade attribution of Monkeypox virus - Mancon, Alessandro; Raccagni, Angelo Roberto; Gagliardi, Gloria; Moschese, Davide; Rizzo, Alberto; Giacomelli, Andrea; Cutrera, Miriam; Salari, Federica; Bracchitta, Fiorenza; Spinello Antinori; Gori, Andrea; Rizzardini, Giuliano; et al. (Emerging microbes & infections, 2024)
Monkeypox virus (MPXV) infection confirmation needs reliable polymerase chain reaction (PCR) assays; in addition, viral clade attribution is a key factor in containment measures, considering a more severe syndrome in clade I and the possibility of simultaneous circulation. This study evaluates the performance of all-in-one STANDARD M10 MPX/OPX (SD BIOSENSOR, South Korea – M10). Frozen samples from 205 subjects were selected and stratified according to routine test results (RealStar® Orthopoxvirus PCR Kit 1.0, Altona DIAGNOTICS, Germany – RS; RS-1): in detail, 100 negative skin lesions (SL) and 200 positive samples at the variable stage of infection were analysed. Positive samples were retested with RS (RS-2). Positive and Negative Percent Agreements (PPA, NPA) were calculated. The median (IQR) Ct values of RS and M10 (OPXV target) assays were highly similar. The PPA of M10 compared to RS-1 was 89.5% considering system interpretation, and 96.0% when the operator classified results as positive if any target was detected; NPA was 100%. Comparing the RS-2 run and M10, an overall concordance of 95.3% between assays was found; however, considering operator interpretation, M10 returned more positive results than RS-2. The occurrence of False-Negative results was likely associated with the influence of thawing on low viral concentration; no False-Positive tests were observed. All samples collected at the time of Mpox diagnosis were positive and M10 correctly attributed the clade (West-Africa/II). The M10 MPX/OPX assay demonstrated high reliability in confirming MPXV infection and clade attribution.